If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -11(x + -2) = 45 Reorder the terms: 8x + -11(-2 + x) = 45 8x + (-2 * -11 + x * -11) = 45 8x + (22 + -11x) = 45 Reorder the terms: 22 + 8x + -11x = 45 Combine like terms: 8x + -11x = -3x 22 + -3x = 45 Solving 22 + -3x = 45 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-22' to each side of the equation. 22 + -22 + -3x = 45 + -22 Combine like terms: 22 + -22 = 0 0 + -3x = 45 + -22 -3x = 45 + -22 Combine like terms: 45 + -22 = 23 -3x = 23 Divide each side by '-3'. x = -7.666666667 Simplifying x = -7.666666667
| 585=(X*3.5^1.25)/22.5^0.5 | | 2/3-x=5/6 | | (4y^2)-1=0 | | 3x^2-5x+7=x^2+2x+1 | | 5.4(4+2x)-7.6=14 | | 6+x/6=-1.68 | | 7/6x-7=10/3x+10 | | 9=19-1y | | 5+a/6=8 | | 4(x-3)=3x-7[4] | | 8y+5x=0 | | 16x^2-24x-5=0 | | 9y^2-36=0 | | 6+1/5x=2 | | 1/2w=-9 | | 3/-8*2/7*-3 | | 36/0.04 | | 8x^2+77x+45=0 | | Ln(lne)=4lnx | | 4/9*7*-3/-8 | | -9/6*2/-5*-7 | | 4-m/3=9 | | 2.1(1.1y+3.4)=-2.4 | | -3xsquared=21x+36 | | 3*1/2 | | E=100(2) | | 5x-7=x+13 | | 4*-5/-3*-2/9 | | 4-2w=(3w-7) | | 5+n/4=10 | | 18x=9y-15 | | -t^3-3t^2+4t+12=0 |